Synchronization between Bidirectional Coupled Nonautonomous Delayed Cohen-Grossberg Neural Networks - Qiming Liu; Rui Xu (Abstract and Applied Analysis)
Based on using suitable Lyapunov function and the properties of M-matrix, sufficient conditions for complete synchronization of bidirectional coupled nonautonomous Cohen-Grossberg neural networks are obtained. The methods for discussing synchronization avoid complicated error system of Cohen-Grossberg neural networks. Two numerical examples are given to show the effectiveness of the proposed synchronization method.